Marine Sponge-Derived Secondary Metabolites Modulate SARS-CoV-2 Entry Mechanisms - Steenblock, Charlotte; Richter, Stefanie; Lindemann, Dirk; Ehrlich, Hermann; Bornstein, Stefan R.; Bechmann, Nicole (Hormone and Metabolic Research, 2023)
The emergence of SARS-CoV 2 caused the COVID-19 pandemic, resulting in numerous global infections and deaths. In particular, people with metabolic diseases display an increased risk of severe COVID 19 and a fatal outcome. Treatment options for severe cases are limited, and the appearance of new virus variants complicates the development of novel therapies. To better manage viral infections like COVID 19, new therapeutic approaches are needed. Marine sponges offer a natural and renewable source of unique bioactive agents. These sponges produce secondary metabolites with various effects, including anti-viral, anti-inflammatory, and anti-tumorigenic properties. In the current study, we investigated the effect of five different marine sponge-derived secondary metabolites (four bromotyrosines and one sesquiterpenoid hydroquinone). Two of these, Avarol and Acetyl-dibromoverongiaquinol reduced the expression of ACE2, the main receptor for SARS-CoV 2, and the alternative receptor NRP1. Moreover, these substances derived from sponges demonstrated the ability to diminish the virus titer in SARS-CoV 2-infected cells, especially concerning the Omicron lineage. However, the reduction was not substantial enough to expect a significant impact on infected humans. Consequently, the investigated sponge-derived secondary metabolites are not likely to be effective to treat COVID 19 as a stand-alone therapy.
Keywords: marine sponges; Aplysina cavernicola; COVID-19; SARS-CoV-2; viral infections; bromotyrosines